Amelioration of diabetes-induced cognitive impairment by Transient Receptor Potential Vanilloid 2 (TRPV2) channel inhibitor: Behavioral and mechanistic study. (October 2020) - Thapak, P.; Bishnoi, M.; Sharma, S.S.
Abstract: Transient receptor potential (TRP) channels are Ca 2+ permeable non-selective cation channels which play a pivotal role in diabetes and diabetic complications. Among diabetic complications, diabetes-induced cognitive impairment is a major CNS complication. The role of several TRP channels has been investigated extensively for their diverse Ca 2+ regulating mechanism, and recently their role has been postulated in the progression of neurodegenerative disorders. However, the role of TRPV2 has not been investigated yet. Therefore, in the present study, the involvement of TRPV2 channels was investigated in diabetes-induced cognitive impairment using TRPV2 inhibitor, tranilast. High glucose exposure in rat C6 glial cells enhances the Ca 2+ -entry through TRPV2 channels. In our in-vivo study, diabetic rats showed increased gene and protein expression of TRPV2 in the hippocampus. Subsequent increase in the acetylcholinesterase activity in the cortex, as well as decrease in the phosphorylation of Ca 2+ /calmodulin-dependent protein kinase II (p-CaMKII-Thr-286), p-GSK-3β (Ser-9), p-CREB (Ser-133) and postsynaptic density protein 95 (PSD-95) in the hippocampus were also observed this led to the impairment in the learning and memory as evident from behavioral parameters such as Morris water maze test, passive avoidance and Y-maze test paradigm. Three-week treatment with tranilast (30 and 100 mg/kg, p.o.) showed improvement in learning and memory associated behaviours (Morris water maze test, passive avoidance, and Y-maze test) by increasing the p-CaMKII (Thr-286), p-GSK-3β (Ser-9), p-CREB (Ser-133) and PSD-95 in the hippocampus. Cortical acetylcholinesterase activity was also reduced by the tranilast. These findings depicted that TRPV2 inhibition may be an effective treatment strategy in diabetes-induced cognitive deficits. Graphical abstract: Image 1 Highlights: Hyperglycemic condition enhanced Ca 2+ influx through TRPV2 channels in C6 rat glioma cells. TRPV2 activation underlies the pathogenesis of cognitive impairment associated with diabetes. Tranilast, a TRPV2 inhibitor attenuated diabetes-induced cognitive impairment. Tranilast improved Ca 2+ ion homeostasis through the improving mRNA level of calcium buffering proteins. Tranilast enhanced the expression of memory associated proteins namely PSD-95, CaMKII and CREB.